2020
DOI: 10.20944/preprints202011.0377.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seagrass Ecosystems of India as Bioindicators of Trace Elements

Abstract: Seagrasses are considered as efficient bioindicators of coastal trace element contamination. This chapter provides an overview on the trace element accumulation, tolerance and biomonitoring capacity of the various seagrass species distributed along the coast of India. A total of 10 trace elements are reported in seagrasses, 11 in sediment and nine in the water column from India. From the 11 seagrass species studied, 60% of research have focused on Syringodium isoetifolium, Cymodocea serrulata, Cymodocea rotund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 64 publications
(105 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, our study also showed that seagrasses at the Korotogo site accumulate more Fe in their tissues than those at Nasese. Similar trend were observed in the whole plant tissues of the three seagrass species reported by Mishra et al (2020) where Fe content was the highest element (795-1886 μg g − 1 ) accumulated in H. pinifolia (Table S4). However, Fe content in the present study (7493-26,137 μg g − 1 ) was much higher than reported by Mishra et al (2020); this could be because the uptake of the elements is influenced by their available concentrations in the surrounding sediment.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…On the other hand, our study also showed that seagrasses at the Korotogo site accumulate more Fe in their tissues than those at Nasese. Similar trend were observed in the whole plant tissues of the three seagrass species reported by Mishra et al (2020) where Fe content was the highest element (795-1886 μg g − 1 ) accumulated in H. pinifolia (Table S4). However, Fe content in the present study (7493-26,137 μg g − 1 ) was much higher than reported by Mishra et al (2020); this could be because the uptake of the elements is influenced by their available concentrations in the surrounding sediment.…”
Section: Discussionsupporting
confidence: 85%
“…Our data shows that Zn was recorded at the highest content in tissues of H. uninervis (52.27 ± 1.76 μg g − 1 ) at Nasese, while the lowest level was recorded in H. pinifolia (22.33 ± 3.22 μg g − 1 ) tissues at Korotogo. The results obtained for Zn in the present study were compared to the results of Mishra et al (2020) for the same three seagrass species where H. pinifolia (35-69.17 μg g − 1 ) had accumulated higher Zn content, while H. ovalis Zn content was within this range (Table S4). Mishra et al (2020) reported that the Cu content of the seagrass (H. ovalis, H. pinifolia and H. uninervis) from India varied from 3.79 to 60.83 μg g − 1 which is comparable to those reported in the three seagrass species in this study (8.7 to 20.5 μg g − 1 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation